Arvon yhteisluonti palveluekosysteemiajattelun valossa - Jalonen, Harri; Kurkela, Kaisa; Rantamäki, Aino; Maijala, Salla; Tuurnas, Sanna (Hallinnon tutkimuksen seura, 2025)
Value Co-Creation through the Service Ecosystem Lens The concept of service ecosystems has gained prominence in public administration and management research for its ability to address the dynamics of complex systems. This paper explores value co-creation within public service ecosystems by examining the relationships between institutions, organizations, and individuals. The study investigates how value cocreation processes function across macro, meso, and micro levels, with a specific emphasis on institutional structures, organizational practices, and individual decisions. Based on interviews with leaders, managers, and experts (n=56) from four public organizations, the research investigates how an ecosystem perspective can be used to expose value co-creation dynamics. The findings contribute to public administration by presenting a framework that underscores the complexity of value creation in collaborative environments.
Keywords: Value co-creation; service ecosystem; public value; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|